Design and Implementation of Electric Shock Device for the Muscles of the Body (Novateur Publications, 2024)
Nobody is surprised by the fact that, according to official figures, the number of medical devices needed in Iraqi hospitals is rising yearly in tandem with the country's population growth at a pace that is appropriate for one million or more people. Naturally, this will result in a rise in the need for hospital and health center construction. Improving civil infrastructure in the field of health care undoubtedly necessitate the expensive importation of several medical devices made by foreign corporations.